Case Report: Evaluation of Patient Diagnosed Perianal Fistula According to Abdellah's 21 Nursing Problems Model - Ilknur Yücel; M. Nasrullah ER (Health and Technology Journal (HTechJ), 2023)
This case report aimed to provide nursing care to the patient diagnosed with Perianal Fistula for the nursing diagnoses in Faye Abdellah's "21 Nursing Problem Theory and North American Nurses Association (NANDA) classification system. Material and Methods: Verbal and written consent was obtained from the patient and the attending physician for the research. Results: He was married at the age of 62. The patient, who has four children and had perianal fistula surgery in 2002, was admitted to the Gastroenterohepatology Polyclinic of a training and research hospital due to increased rectal discharge and constipation recently. disease. There is no known disease in the family history. There is no known history of drug use and known allergy. Conclusion and Suggestions: The case was examined based on Faye Abdellah's "21 Nursing Problem Theory" and the North American Nurses Association (NANDA) Nursing care was given by using the nursing diagnoses in the classification system.